2008
DOI: 10.1108/00070700810868915
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and trust in two organic food chains

Abstract: Purpose -Organic food offers a good case to study the relationships of actors in the food chain, because of its added value based on production methods, the imbalance of power and the different value systems. The obvious problems identified call for solutions that include more efficient collaboration. This paper attempts to determine the presence of collaboration along the Finnish organic food chain, from the farmers to the multiple retailers. Collaboration is approached by focusing on communication and trust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 66 publications
5
94
0
3
Order By: Relevance
“…They also found that the communication quality instead of frequency had significant affect on interpersonal trust. Kottila and Ronni (2008) also found that the quality of information is more important than the frequency of information in creating trust. Huang et al (2008) investigated the role of the communication channels in trust formation between boundary spanning individuals from different organizations.…”
Section: Communication and Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that the communication quality instead of frequency had significant affect on interpersonal trust. Kottila and Ronni (2008) also found that the quality of information is more important than the frequency of information in creating trust. Huang et al (2008) investigated the role of the communication channels in trust formation between boundary spanning individuals from different organizations.…”
Section: Communication and Trustmentioning
confidence: 99%
“…For instance, several studies hypothesized and concluded that it is communication that affects trust formation (Allert & Chatterjee, 1997;Massey & Kyriazis, 2007;Kottila & Ronni, 2008, Webster & Wong, 2008Thomas et al, 2009). In contrast, several other studies found that trust precedes effective communication and is a critical determinant of trust building (Mellinger.…”
mentioning
confidence: 99%
“…Similarly, to the extent that critical aspects of the contract, such as the pricing and grading mechanisms, were not fully explained to the producers, cases of breach of contract and side-selling were inevitable. Porter and Phillips-Howard (1997), Kirsten and Sartorious (2002) and Kottila and Rönni (2008) information asymmetry, which characterized the type of contracting considered in this study. The lack of effective enforcement mechanisms appeared to exacerbate the situation, because the group officials relied on the members to report on their colleagues who attempted to default on the contract.…”
mentioning
confidence: 99%
“…The importance of trust for chain collaboration is widely accepted (Harland, 1999), and it has been regarded as a prerequisite for collaboration (Morgan and Hunt, 1994;Alvarado and Kotzab, 2001;Kottila and Rönni, 2008). Omta et al (2001) stated that in network theory, forms of collaboration are not just based on economic motivations; power and trust are key concepts in this approach.…”
Section: Trustmentioning
confidence: 99%